2021
DOI: 10.1186/s43141-020-00112-z
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase A2 enzyme from the venom of Egyptian honey bee Apis mellifera lamarckii with anti-platelet aggregation and anti-coagulation activities

Abstract: Background Honey bee venom contains various enzymes with wide medical and pharmaceutical applications. Results The phospholipase A2 (PLA2) has been apparently purified from the venom of Egyptian honey bee (Apis mellifera lamarckii) 8.9-fold to a very high specific activity of 6033 U/mg protein using DEAE–cellulose and Sephacryl S-300 columns. The purified bee venom PLA2 is monomeric 16 kDa protein and has isoelectric point (pI) of 5.9. The optimal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…Likewise, the same study demonstrated that MEL and PLA2 (which are also present in A. mellifera syriaca venom) are mainly responsible for this anticoagulant effect. This study supports another finding that showed that PLA2 from the venom of Egyptian honeybee Apis mellifera lamarckii exerts anticoagulant activities [ 37 ].…”
Section: Discussionsupporting
confidence: 91%
“…Likewise, the same study demonstrated that MEL and PLA2 (which are also present in A. mellifera syriaca venom) are mainly responsible for this anticoagulant effect. This study supports another finding that showed that PLA2 from the venom of Egyptian honeybee Apis mellifera lamarckii exerts anticoagulant activities [ 37 ].…”
Section: Discussionsupporting
confidence: 91%
“…Mammadova and ShA (2017) purified and identified the components of bee venom using ion-exchange chromatography with a concentration gradient from 0.01 to 1 M sodium chloride solution on a Servacel-52 column and detected bands, including one with a molecular weight of 22 that they classified as glycoprotein. The band with molecular weight ranging from 19 to 14 KDa might be forms of phospholipase A2 (PLA2) (Pucca et al 2019;Darwish et al 2021), and the band with a molecular weight of ~ 3 kDa which was detected by this technique may confirm the presence of melittin in our venom specimens. This result was matched with previous studies which reported that the bulk of insect venoms that sting humans are composed of various chemical combinations.…”
Section: Discussionmentioning
confidence: 69%
“…PLA2 has a wide range of pharmacological properties, such as the ability to inhibit the growth of cancer cells and to have anti-inflammatory, hepatotoxic, and neuroprotective effects [ 80 , 81 , 82 ]. PLA2 enzyme was purified from A. m. lamarckii venom and displayed anti-coagulant and anti-platelet aggregation activities, making it a promising agent against clot formation [ 83 ].…”
Section: Biological Properties Of Bee Venom From a M Lamarckiimentioning
confidence: 99%